Structural, elastic, optoelectronic, and transport properties of Na-based halide double perovskites Na2CuMX6 (M = Sb, Bi, and X = Cl, Br) as renewable energy materials: A DFT insight - Ayyaz, Ahmad; Murtaza, G.; Umer, M.; Usman, Ahmad; Raza, Hafiz Hamid (Journal of materials research, 2023)
The structural, elastic, optoelectronic, and transport properties of the double perovskites Na 2 CuMX 6 (M = Sb, Bi, and X = Cl, Br) were investigated through the utilization of the DFT-based WIEN2k and BoltzTraP codes. We first explored the structural, electrical, and optical characteristics of Na 2 CuMX 6 using the generalized gradient approximations (GGA) and the GGA modified by the Tran-Balaha modified Becke-Johnson exchange potential (GGA + mBJ). The stability of structures was ensured by the tolerance factor. The mechanical stability was verified by employing Born Criteria, whereas estimated negative formation energy and Gibbs free energy confirmed thermodynamic stability. The indirect electronic bandgap nature was validated for all perovskites by computing electronic band structures. The absorption spectrum and other calculated optical parameters of Na 2 CuMX 6 between 1.7 and 3.4 eV hold notable importance in applications involving solar cells. The BoltzTraP code was utilized to execute the transport property calculations. The computational observations presented in this study hold significant value for future renewable energy applications. Graphical abstract The investigated materials Na2CuMX6 (M = Sb, Bi, and X = Cl, Br) have higher absorption and ZT values, which suggests that all the materials are suitable for photovoltaic and thermoelectric applications.